The Land, Indigenous Identity, and Resistance in Native American and Palestinian Literatures: N. Scott Momaday’s House Made of Dawn and Susan Abulhawa’s Mornings in Jenin as Illustration - BELKHARCHOUCHE, Malika (Journal of Human Sciences, 2025)
The aim of this study is to explore the complex interaction between land and indigenous identity in the literatures of Native Americans and Palestinians and to provide insights into the experiences of the two peoples in their struggle against colonial oppression. Within a post/decolonial framework and adopting an interdisciplinary approach that combines the paradigms of culture, memory, nationhood and sovereignty, this study explores how place and relations to the land have been enacted in Scott Momaday’s House Made of Dawn and Susan Abulhawa’s Mornings in Jenin, and how this connection to the land represents a means of identity affirmation and a symbol of resistance that enables a way of existence in this world. Undertaking this comparative study, which reveals the implicit and explicit connections between two disparate literatures, contributes to understanding interconnected experiences of settler colonialism and the ways indigenous writers contribute with counter-narratives in the nationalist movements of resistance and decolonization.